Determination of Residents’ Attitudes toward Supporting the Heritage Sites Using the Structural Equation Modeling (SEM) in Mansoura Culture Palace, Egypt - Ragheb, Ghada A.; Ragheb, Amany; El-Ashmawy , Rasha (Recent Progress in Science and Technology Vol. 4, 2023)
Improving the performance of the population to support heritage sites is one of the most important contemporary issues. This research aims to discover the relationships and correlations between the impact of the heritage site on the local population, participation in decision-making, and their negative or positive attitude towards the sites. Which eventually influences whether they are in favour of the heritage site's survival, development, or destruction. For the elements of population support and the development of the Mansoura Culture Palace site in Egypt, the study employed a theoretical model. A questionnaire was conducted, and structural equation modeling (SEM) had checked for the validity of the relationships. The correlation discovered between the elements of the model that included dimensions: (population satisfaction with the way of dealing with heritage sites, their sense of place, the involvement of community members in the decision-making action, and between the two variables of the positive or negative attitude of the population, as well as support the heritage site. To determine the degree to which theoretical models of measurement match with field data and to achieve actual development to support heritage sites through the local community, the methodology had been clarified and its statistical indicators had been presented using the CFA, SPSS, and AMOS software. The paper concluded that the residents' support for the survival of the heritage site and its development was positively affected by the residents' positive attitudes toward heritage sites, and vice versa. Population satisfaction and sense of place had an impact on both positive and negative attitudes, but only involvement had an impact on positive sentiments. These findings may serve as a catalyst for the sustainable development of heritage sites.